Vitamin D binding protein correlate with estrogen increase after administration of human chorionic gonadotropin but do not affect ovulation, embryo, or pregnancy outcomes - Chen, Huijun; Yao, Jianghui; Hu, Liang; Liu, Yvonne; Hocher, Johann-Georg; Zhang, Xiaoli; Hasan, Ahmed A.; Lin, Ge; Gong, Fei; Hocher, Berthold (Frontiers in Endocrinology, 2024)
Background: Vitamin D binding protein (DBP) might increase substantially after ovarian stimulation and hence could be associated with IVF/ICSI outcomes because it determines the fraction of free bioavailable 25(OH) vitamin D. In this study, we aim to determine whether DBP is associated with E2 level after ovarian stimulation and IVF/ICSI outcomes.Post-hoc analysis of a prospective observational cohort.Setting: Single-center study.Participants: 2569 women receiving embryo transfer.The main outcomes were oocyte and embryo quality as well as pregnancy outcomes.Results: DBP concentration correlates with E2 on hCG day (=day of inducing ovulation with hCG; correlation coefficient r = 0.118, P＜0.001) and E2 x-fold change to baseline level (r = 0.108, P＜0.001). DBP is also positively correlated with total 25(OH)D (r = 0.689, R2 = 0.475, P＜0.001) and inversely with free 25(OH)D (r = 0.689, R2 = 0.475, P＜0.001), meaning that E2-stimulated DBP synthesis results in a decrease of free 25(OH)D during ovarian stimulation. However, such alteration does not affect IVF/ICSI outcomes when considering confounding factors, such as the number and quality of oocytes nor embryo quality as well as pregnancy outcomes.Conclusions: DBP concentration correlates with the degree of E2 increase after ovarian stimulation. DBP is also positively correlated with total 25(OH)D and inversely with free 25(OH)D, suggesting that the proportion of free 25(OH)D decreases during ovarian stimulation caused by E2-stimulated DBP synthesis. However, such alteration does not affect clinical IVF/ICSI outcomes. Left: correlation between total 25(OH)D and DBP concentration. Right: correlation between free 25(OH)D and DBP concentration.1.